2018
DOI: 10.4067/s0717-92272018000200077
|View full text |Cite
|
Sign up to set email alerts
|

Nivel de conocimientos sobre demencia frontotemporal en una muestra de médicos que evalúan regularmente a pacientes con demencia en Lima-Perú

Abstract: Physicians with specialty in geriatrics, psychiatry and neurology have not received training about the differential diagnosis of dementia, particularly regarding fronto-temporal dementia (FTD). Objective: To assess the level of knowledge of physicians about FTD. Material and Method: The survey was carried out during symposiums and scientific congresses from January 2016 to July 2017. Inclusion criteria: being a general practitioner or specialist in Geriatrics, Neurology and psychiatry whose training process as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
1
10
0
7
Order By: Relevance
“…Nevertheless, future studies will be needed to determine whether this is true or a reflection that the disease is still underrecognized in Latin American counties. Available data from surveys suggest that FLD is not recognized by families and general physicians (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, future studies will be needed to determine whether this is true or a reflection that the disease is still underrecognized in Latin American counties. Available data from surveys suggest that FLD is not recognized by families and general physicians (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…In the decade between 2000 and 2010, most of the publications described clinical, neuropsychological features, and structural imaging of FTD cases (Table 1). In addition, several authors have raised concerns about the difficulties and under-diagnosis of FTD and related disorders in Latin American countries (35)(36)(37)(38).…”
Section: Clinical Presentation and Neuropsychology Of Ftd In Latin Americamentioning
confidence: 99%
“…22,23 This made for a more direct comparison as defined by the similar population and type of setting involved. The majority of BCTs in Peru focus specifically on assessing episodic memory, 4,23 which tends to be impaired during the very early stages of Alzheimer’s disease (AD) but less frequently in other subtypes of dementia. Even more, clear evidence exists that cognitive vascular disorder and vascular dementia occur more frequently in low- and middle-income countries (LMICs).…”
Section: Discussionmentioning
confidence: 99%
“…2 The high level of cases gone undetected and misdiagnosed are proportional to the high number of doctors in LA who haven't received proper training in diagnosing dementia, 3 particularly in the differential diagnosis of less common forms of dementia. 4 On the other hand, it's been shown that doctors and nurses in a primary care setting can, if properly trained, obtain a dementia diagnosis with reasonable accuracy. Clinical data can be obtained during a routine consultation all within the time span of an average primary care office visit.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some studies have suggested that only 3% of dementia patients are diagnosed by their primary care providers in these countries (Chong et al, 2016 ), and it is estimated that 77% of dementia cases in Brazil go undiagnosed (Nakamura et al, 2015 ). Barriers to dementia diagnosis that are particularly relevant to LA include inadequate physician training (Olavarría et al, 2016 ; Mansfield et al, 2019 ), especially among primary care providers (Saxena et al, 2007 ; Parra et al, 2018 ); lack of knowledge about different types of dementia, such as frontotemporal dementia (FTD) (Gleichgerrcht et al, 2011 ; Custodio et al, 2018a ); language barriers; the stigma associated with age-related health problems; insufficient access to healthcare; a lack of diagnostic protocols; and scarcity of neuropsychological services (Custodio et al, 2017c ; Parra et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%